2017
DOI: 10.1016/j.bpj.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

β1-Integrin-Mediated Adhesion Is Lipid-Bilayer Dependent

Abstract: Integrin-mediated adhesion is a central feature of cellular adhesion, locomotion, and endothelial cell mechanobiology. Although integrins are known to be transmembrane proteins, little is known about the role of membrane biophysics and dynamics in integrin adhesion. We treated human aortic endothelial cells with exogenous amphiphiles, shown previously in model membranes, and computationally, to affect bilayer thickness and lipid phase separation, and subsequently measured single-integrin-molecule adhesion kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 67 publications
(68 reference statements)
0
27
0
1
Order By: Relevance
“…As mentioned in Introduction, there is a discrepancy regarding the interplay between receptor-ligand binding and lipid raft coalescence in adhesion experiments with mobile (Huang et al, 2010;Anderson and Roche, 2015) and immobile ligands (Gaus et al, 2006;Mitchell et al, 2009;Evani and Ramasubramanian, 2016;Son et al, 2017). Our results suggest that the discrepancy may be caused by the mobility of ligands in cell-substrate adhesion.…”
Section: Adhesion Of Cell Membrane To the Substrate With Immobile Ligandsmentioning
confidence: 57%
See 1 more Smart Citation
“…As mentioned in Introduction, there is a discrepancy regarding the interplay between receptor-ligand binding and lipid raft coalescence in adhesion experiments with mobile (Huang et al, 2010;Anderson and Roche, 2015) and immobile ligands (Gaus et al, 2006;Mitchell et al, 2009;Evani and Ramasubramanian, 2016;Son et al, 2017). Our results suggest that the discrepancy may be caused by the mobility of ligands in cell-substrate adhesion.…”
Section: Adhesion Of Cell Membrane To the Substrate With Immobile Ligandsmentioning
confidence: 57%
“…Destabilizing raft and protein heterogeneities in vesicles adversely affects the biotin-streptavidin mediated stable adhesion (Zhao et al, 2013). For the adhesion of cells to substrates with immobile ligands mimicking cell-ECM adhesion, experimental studies led to contradictory results regarding the interplay between receptor-ligand binding and coalescence of raft domains (Gaus et al, 2006;Mitchell et al, 2009;Evani and Ramasubramanian, 2016;Son et al, 2017). For example, Son et al (Son et al, 2017) found that integrin-mediated adhesion of human aortic endothelial cells to a substrate facilitates raft domain formation and integrin clustering, which increase the cell-substrate adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Both methods confirm formation of lipid vesicles ( Figure S4 FCS, which was primarily used in this work for observing the changes, is a very sensitive technique for measuring the diffusion changes of molecules. [25][26][27][28] The autocorrelation curves for vesicle tagged and free ATPase show distinct differences in the diffusion time τD, which is directly related to the size of the system according to Stokes-Einstein equation ( Figure S5). To prepare homogeneous and uniform sized ATPase tagged vesicles for FCS measurements, the vesicles were extruded through polycarbonate filters.…”
Section: Resultsmentioning
confidence: 99%
“…The elastic moduli of membranes are fundamental to the understanding of cellular responses to mechanical stimuli (reviewed in (1)), the sensitivity of ion channels to membrane stretch (reviewed in (2)), responses of cilia to fluid flow (reviewed in (3)) and mechanobiological phenomena responsible for health and disease (reviewed in (4)). Derived from area per lipid (APL), these moduli provide input to models that predict membrane bending fluctuations, by which cells sense their surroundings (5), and hydrophobic matching between lipids and proteins, key constants governing lipid phase separation and protein modulation by lipids (6,7). Thus, APL and associated moduli are fundamental mechanistic links between lipid membrane composition and membrane-related biological functions of cells.…”
mentioning
confidence: 99%
“…where kB is Boltzmann constant, T is temperature, and _`a T is the variance of the APL distribution. Assuming a polymer brush model for the lipid bilayer (21), the membrane bending modulus l can be calculated from KA by, l = _ ( nn − % ) T / 24 (7) where DHH is the head-to-head thickness of the bilayer (Table S3) and Do = 1.0 nm is double the distance between the end of the hydrophobic core and center of the…”
mentioning
confidence: 99%